Características clínicas e microbiológicas dos episódios de bacteremias e candidemias em um hospital terciário de grande porte na cidade de Maceió-Alagoas - Tenório, Maria Tereza Freitas [UNIFESP] (2009)
Introduction: Despite the countless breakthroughs regarding the understanding of the pathophysiology of bloodstream infections (BSIs), poor response and persistently high mortality rates are the norm for these patients. In view of the poor knowledge as to the pathological outcome and clinical and microbiological features of these infections within our hospitals, the use of empirical broad-spectrum therapeutics contributes to the emergence of anti-microbial resistance and to higher related costs, without a concomitant reduction in morbidity and mortality rates for these patients. Objectives: Study the clinical outcome, the predisposing factors, and the mortality rate in patients with positive hemoculture during a 30-day period in a tertiary hospital in the city of Maceió. Methodology: A total of 143 patients referred to the hospital between October 2005 and December 2006 took part in the study. They all had at least one positive hemoculture result. All variables were systematically assessed for the study protocol during a 30-day interval. The Chi-square test (SIEGEL) was employed when verifying the association between the qualitative variables. Significance level was at 5%. The statistical analysis software used was the SPSS 15.0 for Windows. Results: At the end of 30 days, 30.1% of the patients had been diagnosed as having only bacteremia and 69.9% had developed sepsis. Out of this latter group, 20.3% went on to severe sepsis and 10.5% suffered from septic shock. Throughout the study, the overall mortality rate for the Hospital was 3.7%, whilst the like rate attributed to this malady was at 37.8%. Mortality rates for patients who had been diagnosed as having bacteremia with no clinical repercussions, with sepsis, severe septis, and septic shock, were, respectively, 9.3%, 50%, 65.5% and 84.6% thirty days after diagnosis. Secondary foci of infection were the most prevalent and were found in the respiratory (32.2%), urinary (14%), and intra-abdominal (7.7%) tracts. Fourteen percent of BSIs were related to the central venous catheter. The medical specialties accounting for most of the cases in this study were neurology, cardiology, general clinical practice, oncology, pediatrics, and neonatology. Their respective figures were 19.6%, 18.9%, 16.8%, 12.6%, 8.4%, and 7.7%. The bacteremia rate in intensive care units (ICUs) was 1.2%, as opposed to 0.33% in wards. Out of these latter cases, 55.12% of them turned into sepsis, while at the ICU this figure rose significantly to 87.69% ( p<0,05). Diabetes mellitus in 26.6% of the patients, chronic renal failure in 21.7%, neuropathy in 29.4%, and chronic obstructive pulmonary disease in 11.2% were the most prevalent comorbidities. Most commonly isolated etiological agents were: coagulase-negative staphylococcus (25.9%), Staphylococcus aureus (21%), Klebsiella pneumoniae (14%), Escherichia coli (9.1%), and Candida Spp. (8.4%). S. aureus was the isolated pathogen in 24.1% of fatal cases. Nosocomial BSIs accounted for 14% of the cases. Conclusion: With regard to prevalence, progression, and mortality attributed to distinct BSI cases, the results herein presented are in compliance with data published elsewhere. In addition, they lend support to the need for setting down the features that clearly define this disease, which in turn will lead to more effective treatment and greater preventive measures.